2023
DOI: 10.1161/strokeaha.122.037936
|View full text |Cite
|
Sign up to set email alerts
|

How Much Attention Do We Pay to Attention Deficits in Poststroke Aphasia?

Abstract: Although language deficits are the primary area of weakness, people with poststroke aphasia often experience challenges with nonlinguistic cognitive skills, including attention processing. The purpose of this review is to synthesize the evidence for the relationship between attention deficits and language deficits in people with poststroke aphasia. Three different types of studies are reviewed: (1) studies exploring whether people with poststroke aphasia exhibit concomitant attention and language deficits, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…There seems to be a neural overlap between attention and post-stroke aphasia. As reported by Varkanitsa et al (2023) , decreased connectivity in the dorsal attention network seems to be related to the severity of aphasia symptoms, and increased connectivity is a result of aphasia treatment. However, today, it is widely accepted that no single brain area is linked to one specific brain function only; rather, neural connectivity is responsible for intact brain functioning ( Herbet and Duffau, 2020 ).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…There seems to be a neural overlap between attention and post-stroke aphasia. As reported by Varkanitsa et al (2023) , decreased connectivity in the dorsal attention network seems to be related to the severity of aphasia symptoms, and increased connectivity is a result of aphasia treatment. However, today, it is widely accepted that no single brain area is linked to one specific brain function only; rather, neural connectivity is responsible for intact brain functioning ( Herbet and Duffau, 2020 ).…”
Section: Introductionmentioning
confidence: 52%
“…We found no increase in the neuropsychological test values for attention assessment, the P300 amplitudes, or the connectivity tasks. It might be that a potential link between the attention network ( Varkanitsa et al, 2023 ) and the language network ( Hertrich et al, 2020 ) cannot be influenced or measured by using a visual P300 BCI while with an auditory P300 BCI, a beneficial effect on post-stroke aphasia was suggested ( Musso et al, 2022 ). Furthermore, the P300 amplitudes in this study were not comparable to the P300 amplitudes found in healthy participants ( Dejanović et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various pathologies that disrupt the functioning of the nervous system and destabilize mental processes disrupt the processes of arbitrary regulation, which subsequently affects human behavioral activity in various parameters. Initially, arbitrary regulation is a predictor of the effectiveness of a person's life in both personal and every day, as well as social and professional manifestations [19]. It is from the level of its development and preservation (stability of health) in the factors inherent in healthy ontogenesis that the entire further line of human activity and selfmanifestation, his reactions in society, in the world around him, his self-manifestation and personal influence on surrounding people and the world as a whole will be reflected.…”
Section: Resultsmentioning
confidence: 99%
“…Varkanitsa et al 12 examine the impact of attentional processing on aphasia after stroke. As the authors note, increasing evidence suggests that many people with aphasia also experience challenges with global cognitive functions, including attention, learning, and memory.…”
Section: Aphasia and Attentional Processingmentioning
confidence: 99%